Pembelajaran Kitab Nihayatuz Zain Metode Syawir Dalam Penguatan Pengetahuan Fikih Santri Di Pondok Pesantren Nurul Hidayah Mangli Jember - Lailatul Azizah; Zainal Anshari (Akademika, 2025)
This study addresses the limited fiqh understanding among students at Pondok Pesantren Nurul Hidayah Mangli Jember due to time constraints. The Nihayatuz Zain book is used for its relevant content, while the syawir method is applied to enhance comprehension. The research aims to describe the implementation of kitab learning, the use of the syawir method, and the improvement of students’ fiqh knowledge. The focus of this research includes: (1) How is the Nihayatuz Zain book taught at Pondok Pesantren Nurul Hidayah Mangli Jember? (2) How is the syawir method implemented in the learning process? (3) How is students’ fiqh knowledge strengthened at the pesantren. The research objectives are: (1) To describe the process of book learning at Pondok Pesantren Nurul Hidayah Mangli Jember, (2) To explain how the syawir method is applied in the learning activities, and (3) To describe how students’ understanding of fiqh is reinforced through the learning process.. This study uses a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The data analysis involved data reduction, data presentation, and drawing conclusions. The findings show that: (1) Nihayatuz Zain learning is well-planned, covering time, place, objectives, and relevant material. (2) The syawir method runs in three stages: opening, discussion, and closing. (3) Students' fiqh understanding improves through better comprehension, argumentation with Islamic sources, and real-life application of Islamic rulings